Anthocyanin, Antioxidant and Metabolite Content of Butterfly Pea Flower (Clitoria ternatea L.) Based on Flowering Phase - Juswardi, Juswardi; Yuliana, Rina; Tanzerina, Nina; Harmida, Harmida; Aminasih, Nita (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
The butterfly flowers (Clitoria ternatea L.) are used as natural dyes and herbal medicines because they contain metabolites, anthocyanins and antioxidants. The content of these metabolites is influenced by the phase of flower development. This study aims to determine the levels of anthocyanins, antioxidants and metabolites of butterfly pea flowers from different flowering phases. The Butterfly flower collection was taken from the village of Mulyaguna, Teluk Gelam, Ogan Komering Ilir, South Sumatra. The extraction was carried out with 70% ethanol solvent, and determination of the amount of anthocyanin content by spectrophotometry, antioxidant content by DPPH method, and metabolite compounds by GC-MS. Data on anthocyanin and antioxidant content were analyzed with averages and standard deviations, and GC-MS chromatograms were traced for compounds with reference to the PubChem, KEGG, ChEBI, PlantCyc, and Spectrabase websites, which then determined the dominant compound group. The results of the study on blooming butterfly pea flowers found that the antioxidant content was 6.58 ppm, higher than that of bud flowers, which were 2.55 ppm, and wither flowers, which were 1.74 ppm. The anthocyanin content of the blooming butterfly pea flower was 40.33 ppm, the withering flower was 4.36 ppm, and the bud flower was 3.60 ppm. The dominant metabolites were identified as fatty acids, organic acids, aromatics and flavanoids, followed by differences in antioxidant and anthocyanin content in the flowering phase of the butterfly pea flower